Extraction of organophosphorus pesticides by carbon‐coated Fe3O4 nanoparticles through response surface experimental design. Issue 2 (24th November 2015) - Maddah, Bozorgmehr; Alidadi, Sattar; Hasanzadeh, Mahdi
Abstract : In this paper, carbon‐coated Fe3 O4 nanoparticles were successfully synthesized and used as a magnetic solid‐phase extraction absorbent for the preconcentration and extraction of organophosphorus pesticides in environmental water samples. The carbon‐coated Fe3 O4 nanoparticles were characterized by transmission electron microscopy, X‐ray powder diffraction, Fourier transform infrared spectroscopy, and vibrating sample magnetometry. The determination of organophosphorus pesticides in water samples with carbon‐coated Fe3 O4 nanoparticles was investigated by high‐performance liquid chromatography with a diode array detector. Furthermore, the response surface model based on the central composite design was applied to quantitatively investigate the effect of some important variables influencing the extraction efficiency, such as pH, treatment time, amount of nanoparticle sorbents, and amount of salt and to find the optimized conditions providing the highest extraction efficiency. Under optimized conditions, the calibration curve was linear in the range of 0.5–15.0 ng/mL with a regression coefficient of 0.9948, 0.9958, and 0.9931 for fenitrothion, diazinon, and ethion, respectively. The obtained results showed that this analytical method would be useful for the analysis of fenitrothion, diazinon, and ethion in tap water with high precision and accuracy.